Effect of long term inhaled corticosteroid therapy on adrenal suppression, growth and bone health in children with asthma - Anuradha KWDA; Prematilake GLDC; Batuwita BAUI; Kannangoda KASR; Hewagamage US; Wijeratne S; Lankatilake Kantha; de Silva KSH (BMC, 2019)
Abstract Background Inhaled corticosteroids (ICS) are the most effective treatment for children with persistent asthma. However adverse effects of ICS on Hypothalamo Pituitary Adrenal (HPA) axis, growth and bone metabolism are a concern. Hence the primary objective of this study was to describe the effects of long term inhaled corticosteroid therapy (ICS) on adrenal function, growth and bone health in children with asthma in comparison to an age and sex matched group of children with asthma who were not on long term ICS. Describing the association between the dose of ICS and duration of therapy on the above parameters were secondary objectives. Method Seventy children with asthma on ICS and 70 controls were studied. Diagnosis of asthma in selected patients was reviewed according to the criteria laid down by GINA 2018 guidelines. The estimated adult heights were interpreted relative to their Mid Parental Height (MPH) range. Serum calcium, alkaline phosphatase and vitamin D levels were analyzed in both groups and cortisol value at 30 min following a low dose short synacthen test was obtained from the study group. The average daily dose of ICS (Beclamethasone) was categorized as low, medium and high (100-200, 200-400, > 400 μg /day) respectively according to published literature. Results Heights of all children were within the MPH range. There was no statistically significant difference in the bone profiles and vitamin D levels between the two groups (Ca: p = 0.554, vitamin D: p = 0.187) but vitamin D levels were insufficient (< 50 nmol/l) in 34% of cases and 41% of controls. Suppressed cortisol levels were seen in 24%. Doses of ICS were low, medium and high in 56, 32 and 12% of children respectively. The association between adrenal suppression with longer duration of therapy (p < 0.01) and with increasing dose of ICS (p < 0.001) were statistically significant. Conclusion ICS had no impact on the growth and bone profiles but its dose and duration were significantly associated with adrenal suppression.